GRAMMAR CONSCIOUSNESS-RAISING: RESEARCH, THEORY, AND APPLICATION - Setiono Sugiharto (Indonesian JELT, 2006)
This article reviews a number of studies that proved the efficacy of consciousness-raising (C-R), showing at the same time the inherent flaws that these studies suffer. It then proceeds to discuss the theoretical assumptions underpinning C-R, the application and the intended outcomes of C-R. In doing this, teachers can obtain a comprehensive picture of C-R, and in particular understand its typical characteristics that differentiate it from the traditional teaching method such as the Grammar Translation. Implications from C-R studies for language teaching are also discussed.  Keywords: consciousness-raising, the Grammar Translation.